In Vitro Activity Test of A-Glucosidase Enzyme Inhibition of Moringa oleifera L. Leaves Extract - Irma Pattola; St. Maryam; Rais Razak (Universitas Muslim Indonesia, 2022)
Diabetes Mellitus (DM) is a group of disease characterized by an increase in insulin. Moringa oleifera leaves contain chemical properties such as tannins, steroids, triterpenes, flavonoids, saponins, anthraquinones and alkaloids. These chemical compounds can affect a variety of biological activities and one of the is antidiabetic. The research aimed to study the potential of Moringa oleifera extract in relation to the a-glucosidase enzyme which is one of the transitions of antidiabetic drugs based on IC50 values. In this study moringa leaves were extracted by maceration method using 96% ethanol solvent. The inhibitory activity testing uses an ELISA (Enzyme-linked Immunosorbent Assay) reader measured at 405 nm wavelength with a comparator of the acarbose because it is an antidiabetic drug of the glucosidase enzyme inhibitor group. The results of the a-glucosidase enzyme showed that the a-glucosidase enzyme activity was inhibited by the ethanol extract of Moringa oleifera L. with C50 value 84,238 µg/mL included in the less active category.